2014
DOI: 10.3201/eid2005.131298
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Leukemia Virus DNA in Human Breast Tissue

Abstract: Bovine leukemia virus (BLV), a deltaretrovirus, causes B-cell leukemia/lymphoma in cattle and is prevalent in herds globally. A previous finding of antibodies against BLV in humans led us to examine the possibility of human infection with BLV. We focused on breast tissue because, in cattle, BLV DNA and protein have been found to be more abundant in mammary epithelium than in lymphocytes. In human breast tissue specimens, we identified BLV DNA by using nested liquid-phase PCR and DNA sequencing. Variations from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 23 publications
6
153
1
2
Order By: Relevance
“…[36][37][38] Further evidence for the possible transmission of BLV from cattle to humans was the detection of BLV sequences by PCR in 44% of breast tissues, and the most striking finding was BLVp24 expression detected by immunohistochemistry on the secretory epithelium of the mammary gland. 39 A subsequent case-control study showed BLV sequences in samples from breast cancer patients being at a level twice that in normal breast tissue sections, concluding that the presence of BLV in breast tissues was associated with breast cancer. 40 Although the precedent cited studies suggested an association between BLV and breast cancer, the evidence is still controversial.…”
Section: Juliarena Et Almentioning
confidence: 99%
“…[36][37][38] Further evidence for the possible transmission of BLV from cattle to humans was the detection of BLV sequences by PCR in 44% of breast tissues, and the most striking finding was BLVp24 expression detected by immunohistochemistry on the secretory epithelium of the mammary gland. 39 A subsequent case-control study showed BLV sequences in samples from breast cancer patients being at a level twice that in normal breast tissue sections, concluding that the presence of BLV in breast tissues was associated with breast cancer. 40 Although the precedent cited studies suggested an association between BLV and breast cancer, the evidence is still controversial.…”
Section: Juliarena Et Almentioning
confidence: 99%
“…Parameter 1 -Report of zoonotic human cases (anywhere) BLV genome sequences have been found in breast cancer tissue, but no evidence has indicated an aetiological role of BLV in human disease (Buehring et al, 2001(Buehring et al, , 2014(Buehring et al, , 2015Baltzell et al, 2009). …”
Section: Presencementioning
confidence: 99%
“…BLV has been known and studied as an infectious agent in cattle; however, there are reports of this virus in humans [6,7,9] even though the mechanism by which the virus has reached such host has still not been clarified. Buehring et al [15,23] highlighted three main hypotheses for the viral entry to humans.…”
Section: Resultsmentioning
confidence: 99%
“…PCR tests were done using Roche PCR master mix with specific primers (0·8 pmol/μl) for the aforementioned genes. Both bovine GAPDH and gag primers were previously reported by Buehring et al [6]. An 857 bp fragment was amplified for the bovine GAPDH gene and a 385 bp fragment for gag.…”
Section: Pcr Amplification: Multiplex and Nested Pcrmentioning
confidence: 99%
See 1 more Smart Citation